Navigating the Intersection of Social Media and Countering Violent Extremism in Pakistan - Amber Javed; Noor Elahi; Bahadar Nawab, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
In the fight against extremism, social media is becoming crucial for shaping public opinion and promoting peace. Pakistan has a growing emphasis on building a counternarrative to combat extremism. This study focuses on the potential and effectiveness of social media in promoting counter-narratives against extremism and combating radicalization in Pakistan. The research emphasizes the role of various actors, such as government institutions, journalists, and peacebuilders in? The data was collected through questionnaires from 120 journalists and peacebuilders across Pakistan. The results indicate that social media is a popular source of information but is considered unreliable and inaccessible to many regions and populations. The analysis of social media platforms emphasized the significance of reaching the appropriate audience through the appropriate platform. In conclusion, the study shows that social media has the potential to play a crucial role in countering extremism in Pakistan. However, both government and non-government organizations need to harness its power effectively. The study suggests that social media may not be sufficient in isolation and recommends a multi-faceted approach that utilizes the strengths of various media sources. Further research is required to explore ways to improve the use of social media for peacebuilding goals.